Narrow band imaging versus lugol chromoendoscopy to diagnose squamous cell carcinoma of the esophagus: a systematic review and meta-analysis. Issue 1 (December 2017) - Morita, Flavio; Bernardo, Wanderley; Ide, Edson; Rocha, Rodrigo; Aquino, Julio; Minata, Mauricio; Yamazaki, Kendi; Marques, Sergio; Sakai, Paulo; de Moura, Eduardo
Abstract Background In the early stage esophageal cancer, changes in the mucosa are subtle and pass unnoticed in endoscopic examinations using white light. To increase sensitivity, chromoscopy with Lugol's solution has been used. Technological advancements have led to the emergence of virtual methods of endoscopic chromoscopy, including narrow band imaging (NBI). NBI enhances the relief of the mucosa and the underlying vascular pattern, providing greater convenience without the risks inherent to the use of vital dye. The purpose of this systematic review and meta-analysis was to evaluate the ability of NBI to diagnose squamous cell carcinoma of the esophagus and to compare it to chromoscopy with Lugol's solution. Methods This systematic review included all studies comparing the diagnostic accuracy of NBI and Lugol chromoendoscopy performed to identify high-grade dysplasia and/or squamous cell carcinoma in the esophagus. In the meta-analysis, we calculated and demonstrated sensitivity, specificity, and positive and negative likelihood values in forest plots. We also determined summary receiver operating characteristic (sROC) curves and estimates of the areas under the curves for both per-patient and per-lesion analysis. Results The initial search identified 7079 articles. Of these, 18 studies were included in the systematic review and 12 were used in the meta-analysis, for a total of 1911 patients. In per-patient and per-lesion analysis, the sensitivity, specificity, and positive and negative likelihood values for Lugol chromoendoscopy were 92% and 98, 82 and 37%, 5.42 and 1.4, and 0.13 and 0.39, respectively, and for NBI were 88 and 94%, 88 and 65%, 8.32 and 2.62, and 0.16 and 0.12, respectively. There was a statistically significant difference in only specificity values, in which case NBI was superior to Lugol chromoendoscopy in both analyses. In the per-patient analysis, the area under the sROC curve for Lugol chromoendoscopy was 0.9559. In the case of NBI, this value was 0.9611; in the per-lesion analysis, this number was 0.9685 and 0.9587, respectively. Conclusions NBI was adequate in evaluating the esophagus in order to diagnose high-grade dysplasia and squamous cell carcinoma. In the differentiation of those disorders from other esophageal mucosa alterations, the NBI was shown to be superior than Lugol.